Analisis Perceived Quality, Perceived Enjoyment, dan Perceived Price Terhadap Perceived Value dan Purchase Intention pada Layanan Subscription Video on Demand (SVOD) - Ni Ketut Kahar Tunjung Santi Dewi; Usep Suhud; Meta Bara Berutu (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This study aims to analyze the influence of Perceived Quality, Perceived Enjoyment, and Perceived Price on Perceived Value, as well as its implications for Purchase Intention among potential Netflix customers. This research is motivated by the increasingly fierce competition in Streaming Video on Demand (SVoD) services, making it important to understand how consumer perceptions are formed before they actually use the service. This study employs a quantitative approach using the Structural Equation Modeling (SEM) method. Primary data were collected through an online questionnaire and analyzed using SPSS version 25 and AMOS version 29. The results show that the three perception variables significantly influence Perceived Value, which in turn also significantly influences Purchase Intention. These findings provide strategic implications for Netflix in attracting potential customers by enhancing perceived value.